Room‐Temperature Ferromagnetic Insulating State in Cation‐Ordered Double‐Perovskite Sr2Fe1+xRe1−xO6Films. Issue 4 (29th November 2018) - Sohn, Changhee; Skoropata, Elizabeth; Choi, Yongseong; Gao, Xiang; Rastogi, Ankur; Huon, Amanda; McGuire, Michael A.; Nuckols, Lauren; Zhang, Yanwen; Freeland, John W.; Haskel, Daniel; Lee, Ho Nyung
Abstract: Ferromagnetic insulators (FMIs) are one of the most important components in developing dissipationless electronic and spintronic devices. However, FMIs are innately rare to find in nature as ferromagnetism generally accompanies metallicity. Here, novel room‐temperature FMI films that are epitaxially synthesized by deliberate control of the ratio between two B‐site cations in the double perovskite Sr2 Fe1+ x Re1‐ x O6 (−0.2 ≤ x ≤ 0.2) are reported. In contrast to the known FM metallic phase in stoichiometric Sr2 FeReO6, an FMI state with a high Curie temperature ( T c ≈ 400 K) and a large saturation magnetization ( M S ≈ 1.8 µB f.u. −1 ) is found in highly cation‐ordered Fe‐rich phases. The stabilization of the FMI state is attributed to the formation of extra Fe 3+ Fe 3+ and Fe 3+ Re 6+ bonding states, which originate from the relatively excess Fe ions owing to the deficiency in Re ions. The emerging FMI state created by controlling cations in the oxide double perovskites opens the door to developing novel oxide quantum materials and spintronic devices. Abstract : Ferromagnetic insulators, innately rare in nature, are important components for realizing dissipationless quantum electronic/spintronic devices and solid‐state quantum computing. Room‐temperature ferromagnetic insulating films are successfully synthesized by deliberate control of the cation ratio and ordering in oxide double perovskites Sr2 Fe1+ x Re1− x O6, which can be used for future development of advanced quantum devices working at ambient temperature.